2022
DOI: 10.3390/cancers14112809
|View full text |Cite
|
Sign up to set email alerts
|

Management of Older Adults with Locally Advanced Head and Neck Cancer

Abstract: Thirty percent of patients with head and neck squamous cell carcinoma (HNSCC) are at least 70 years of age. This number continues to rise as life expectancy continues to increase. Still, older adults with HNSCC remain underrepresented in clinical trials, resulting in ambiguity on optimal management. Older adults are a complex patient population, often requiring increased support due to issues relating to functional and performance status, medical comorbidities, and medication management. Furthermore, in older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 118 publications
1
20
0
Order By: Relevance
“…The ideal treatment of older patients with LA-HNSCC is a matter of debate, considering the limited evidence due to underrepresentation or exclusion of older patients from landmark trials. 19 The value of systemic treatment given concomitantly with definitive radiotherapy is a controversial topic, as there was no significant benefit of adding chemotherapy shown in the MACH-NC study. 3 The increasing prevalence of frailty, comorbidities, and the higher vulnerability to chemotherapy-related toxic effects in older adults with HNSCCs may all contribute to the decreasing efficacy of chemoradiation in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ideal treatment of older patients with LA-HNSCC is a matter of debate, considering the limited evidence due to underrepresentation or exclusion of older patients from landmark trials. 19 The value of systemic treatment given concomitantly with definitive radiotherapy is a controversial topic, as there was no significant benefit of adding chemotherapy shown in the MACH-NC study. 3 The increasing prevalence of frailty, comorbidities, and the higher vulnerability to chemotherapy-related toxic effects in older adults with HNSCCs may all contribute to the decreasing efficacy of chemoradiation in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort study of 1044 older adults with LA-HNSCC, chemoradiation was associated with longer survival than radiotherapy alone, whereas the addition of cetuximab to radiotherapy was not associated with improved survival. The ideal treatment of older patients with LA-HNSCC is a matter of debate, considering the limited evidence due to underrepresentation or exclusion of older patients from landmark trials . The value of systemic treatment given concomitantly with definitive radiotherapy is a controversial topic, as there was no significant benefit of adding chemotherapy shown in the MACH-NC study .…”
Section: Discussionmentioning
confidence: 99%
“…Our investigators hypothesize that this hypofractionated regimen will significantly improve treatment tolerance, with no change in disease control efficacy at 6 months. 108 , 109 …”
Section: Treatmentmentioning
confidence: 99%
“…Our investigators hypothesize that this hypofractionated regimen will significantly improve treatment tolerance, with no change in disease control efficacy at 6 months. 108,109 There are conflicting data regarding RT-related toxicity in the elderly population, with studies reporting either increased or similar RT-induced toxicity in elderly patients compared to a younger cohort; 10,19,[110][111][112] however, the association between increased RT toxicity and the addition of chemotherapy in the elderly population is well established. 10,110 A review of Radiation Therapy Oncology Group (RTOG) CRT trials for HNSCC demonstrated significantly higher rates of severe late toxicity (defined as chronic grade 3+ pharyngeal/laryngeal toxicity and/or requirement for a feeding tube ≥2 years after registration and/or potential treatment-related death within 3 years) in the elderly cohort.…”
Section: Dovepressmentioning
confidence: 99%
“…There are an estimated 650 000 new cases and 350 000 deaths annually worldwide, representing approximately 6% of all cases 1 . In all tumors that originated from the head and neck, including the mouth, oropharynx, hypopharynx, and larynx, 95% of them are squamous cell carcinoma in histological type 2 . The incidence of HNC varies greatly in different regions of the world.…”
Section: Introductionmentioning
confidence: 99%